Medidas repetidas no tempo realizadas por ultrassom em ovelhas de descarte em diferentes estágios fisiológicos - Pinheiro, Rafael Silvio Bonilha [UNESP]; Jorge, André Mendes [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Yokoo, Marcos Jun Iti (My University, 2014)
Some measurements carried out by ultrasound in the Longissimus dorsi between the 12th and 13th ribs were monitored, aiming to know the changes in the muscular and adipose tissues in that muscle and the connections of these measurements with body weight (BW) and body condition score (BCS) of ewes in different stages (physiological stages and experimental periods). Ewes were arranged into the following treatments: EL = ewes which remained in lactation for 60 days with their respective lambs and slaughtered one day after weaning; EWL = ewes which remained in lactation for 60 days with their respective lambs and one more period of approximately 30 days without the lambs and slaughtered afterwards; and ENC = ewes which did not give birth during the year. Ultrasound measurements were carried out in the beginning, middle and end of the experiment (every 21 days), as well as BW and BCS of ewes. There was not interaction between periods and experimental treatments for BW and BCS of ewes. It was concluded that the use of ultrasound allows monitoring changes that occur with the subcutaneous fat and Longissimus dorsi of ewes. Those changes occur more frequently in intervals of 42 days (muscular and adipose tissues).
Measurements repeated in time carried out by ultrasound in discard ewes in different physiological stages
Keywords: Body condition; Body weight; Loin eye area; Sheep; Subcutaneous fat thickness